Africa in the 21st century toward a new future - Mazama, Ama. (New York Routledge, 2007)
Africa in the 21st Century: Toward a New Future brings together some of the finest Pan African and Afrocentric intellectuals to discuss the possibilities of a new future where the continent claims its own agency in response to the economic, social, political, and cultural problems which are found in every nation. The volume is structured around four sections: I. African Unity and Consciousness: Assets and Challenges; II. Language, Information, and Education; III. African Women, Children and Families; and IV. Political and Economic Future of the African World. In original essays, the authors raise the level of discourse around the questions of integration, pluralism, families, a federative state, and good governance. Each writer sees in the continent the potential for greatness and therefore articulates a theoretical and philosophical approach to Africa that constructs a victorious consciousness from hard concrete facts. This book will interest students and scholars of the history and politics of Africa as well as professional Africanists, Africologists, and international studies scholars who are inclined toward Africa.
Includes bibliographical references and index.
Keywords: Africa-Social conditions, Africa-Economic conditions Africa-Political conditions Africa-Forecasting